2020
DOI: 10.1002/anie.202002089
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol‐Mediated Assembly of Proteins for Engineering Functional Materials

Abstract: Functional materials composed of proteins have attracted much interest owing to the inherent and diverse functionality of proteins. However, establishing general techniques for assembling proteins into nanomaterials is challenging owing to the complex physicochemical nature and potential denaturation of proteins. Here, a simple, versatile strategy is introduced to fabricate functional protein assemblies through the interfacial assembly of proteins and polyphenols (e.g., tannic acid) on various substrates (orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 47 publications
3
164
0
Order By: Relevance
“…Polyphenols and MPNs were first used as universal coating materials benefiting for the versatile adhesive property of polyphenols to almost all kinds of surfaces, regardless of the surface chemistries. [260][261][262][263][264][265][266] As a result, polyphenols have been used as coating materials to functionalize a host of nanomaterials for biomedical applications. [267][268][269][270] The polyphenols coated on the surfaces of various nanomaterials can easily interact with the amine and thiol groups via Michael-type addition or Schiff base reaction, self-polymerize in alkaline media, and chelate with metal ions, endowing the resulting nanomaterials with desired structures, properties, and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols and MPNs were first used as universal coating materials benefiting for the versatile adhesive property of polyphenols to almost all kinds of surfaces, regardless of the surface chemistries. [260][261][262][263][264][265][266] As a result, polyphenols have been used as coating materials to functionalize a host of nanomaterials for biomedical applications. [267][268][269][270] The polyphenols coated on the surfaces of various nanomaterials can easily interact with the amine and thiol groups via Michael-type addition or Schiff base reaction, self-polymerize in alkaline media, and chelate with metal ions, endowing the resulting nanomaterials with desired structures, properties, and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular docking analysis also showed that PUE not only interacted with the positively charged lysine residue, but also interacted with the negatively charged glutamic acid residue [4]. This may also contribute to the decrease in negative charge [25,26].…”
Section: Characterization Of Oil-in-water Emulsions Prepared Using Wpi-pue Compositesmentioning
confidence: 88%
“…Though the presence of PUE increased the ionic stability, both the WPI and the WPI-PUE emulsions were unstable in the presence of salt. The WPI-PUE composites might also disassemble because of electrostatic shielding in the presence of NaCl [26].…”
Section: Influence Of Ionic Strength On the Emulsionmentioning
confidence: 99%
“…Similar results were obtained with a higher release in the presence of 150 mM NaCl in the case of citrate films, which confirms the contribution of ionic interactions in these films. 46 Concerning E. Coli, a decrease in the normalized growth of 45% was observed after 24 h of contact with (COL/TA) 7 citrate films ( Figure S13 in the SI). It is known that the bactericidal activity of tannins is lower against gram-negative bacteria than against gram-positive bacteria.…”
Section: D a Bmentioning
confidence: 95%
“…Polyphenols can have multiple interactions with proteins depending on their physico-chemical parameters, such as molecular weight, hydrophobicity and isoelectric point. 46 Tannins are known to interact with collagen 47 and other proline-rich proteins 48 ) was calculated from the heat measured at each step of the titration subtracting the heat of the control experiments, i.e. buffer in buffer and titrant dilution in buffer ( Figure 2).…”
Section: D a Bmentioning
confidence: 99%